Transformasi UMKM Rupat Utara: Strategi Terpadu Pelatihan Pengembangan Kemasan Produk dan Optimalisasi Pemasaran Digital - Susanti, Hevi; Angela, Sesdia; Pane, Rico Purnawandi; Susanto, Agus; Wicaksono, Baskoro; Hayati, Isnaria Rizki (Civiliza Publishing, 2025)
This community service program aims to increase the capacity of MSMEs in North Rupat through a comprehensive approach that includes digital skills training and strengthening business management. There are three main problems faced by business actors: first, the low mastery of digital technology; second, less attractive product packaging; and third, marketing strategies that are not yet effective. To overcome this, this program is designed with four main focuses, namely digital marketing, packaging development, creative content creation, integrated business management, and business communication skills development. The implementation uses a hybrid method that combines face-to-face meetings with online mentoring. This program began with a needs survey and focus group discussions (FGD) to prepare training materials that are right on target. The results include improving the quality of digital marketing content, improving product packaging design, and expanding marketing networks which have an impact on increasing business turnover. In the long term, this program is expected to create MSMEs that are independent, highly competitive in the digital era, and able to reach a wider market, including cross-regional markets. In addition to solving technical problems, the program is also committed to building a sustainable business ecosystem through a holistic empowerment approach. This service activity is also inseparable from the role of students in the assistance that is carried out, this activity is expected to make MSMEs understand how to technically use applications in smartphones to produce content, understand how to make attractive packaging designs based on local wisdom and can take advantage of various new media and social media to implement digital marketing. For this reason, cooperation in various teams is needed in the implementation of midwifery.